Clinicopathological analysis of appendiceal goblet cell adenocarcinoma with peritoneal metastasis: World Health Organization grade predicts survival following cytoreductive surgery with intraperitoneal chemotherapy. Issue 5 (27th September 2020) - Shyu, Susan; Choudry, Haroon; Hall, Lauren; Pingpank, James; Holtzman, Matthew; Bartlett, David; Pai, Reetesh K
Abstract : Aims: Peritoneal spread is the most common route of metastasis in appendiceal goblet cell adenocarcinoma. The aim of this study was to assess the prognostic significance of the World Health Organization (WHO) 5th edition grading criteria in peritoneal metastases of goblet cell adenocarcinoma. Methods and results: We evaluated the clinicopathological features and survival of 63 patients with peritoneal metastasis of goblet cell adenocarcinoma who underwent cytoreductive surgery with hyperthermic intraperitoneal chemoperfusion (CRS‐HIPEC), stratified according to the WHO 5th edition and the Tang et al . grading schemes. The patients were also compared with 120 patients with peritoneal metastasis of appendiceal mucinous neoplasia. Most (73%) peritoneal metastases of goblet cell adenocarcinoma were WHO Grade 3 (G3), there being fewer cases of Grade 2 (G2) (16%) and Grade 1 (G1) (11%) disease. No significant differences in overall survival were observed between WHO G1 and G2 tumours or between the three Tang grades. In the multivariable model of survival, WHO G3 [hazard ratio (HR) 2.81, 95% confidence interval (CI) 1.02–7.70] and the presence of >50% extracellular mucin (HR 2.30, 95% CI 1.09–4.88) were associated with reduced overall survival for patients with goblet cell adenocarcinoma. As compared with patients with peritoneal metastasis of mucinous neoplasia, patients with goblet cell adenocarcinoma had significantly reduced survival (median overall survival of 37 months versus 102 months, P < 0.001), which was attributed to the reduced survival of patients with G1/G2 goblet cell adenocarcinoma as compared with patients with G1 mucinous neoplasia (median survival of 98 months versus 204 months, P < 0.001). Conclusions: Grade of peritoneal goblet cell adenocarcinoma determined according to the WHO 5th edition criteria is a clinically relevant measure that independently predicts survival in patients treated with CRS‐HIPEC.